From ‘publish or perish’ to ‘publish with purpose’: perspectives from young adults with lived and living experience on transforming academic publishing in patient-oriented research - Sandy Rao; Rae Jardine; Abitha Suthakaran; Laetitia Satam; Antoaneta A. Todorova; Ysabelle Tumaneng; Julien Quickstad (Research Involvement and Engagement)
Abstract Background This commentary article critically assesses the inclusion and recognition of young adults with lived and living experiences (YALLE) in academic publishing. Stemming from our involvement in a health research study, this analysis interrogates the disparity between the stated importance of YALLE contributions in health research and their actual recognition, specifically in academic publications, which serve as the principal “currency” in research. This tokenism limits the potential for their unique insights to substantially enrich the discourse and dissemination of knowledge. Set against a backdrop of systemic biases and structural barriers, this discussion underscores the persistent minoritization of YALLE, despite increasing nominal recognition within academic and health research communities. Main text The commentary begins by placing the engagement of young adults in health research within its current context, showing that this inclusion often remains superficial, serving more as a symbolic gesture toward inclusivity rather than fostering genuine participatory research. It critiques the implicit biases within institutional frameworks that continue to shape research culture detrimentally, thus stifling the transformative potential of research led and partnered by young adults. The core of the narrative addresses the complex challenges faced by YALLE, including discrimination, underrecognition, and inadequate participatory roles in research processes. These issues are magnified by the prevalent “publish or perish” culture in academia, which prioritizes the quantity of scholarly output over the quality and inclusivity of research contributions. Conclusions The commentary advocates for a crucial shift in academic publishing to genuinely appreciate and integrate the contributions of young adults. We call for a transition from a “publish or perish” model to a “publish with purpose” approach, which necessitates rethinking what is considered valuable knowledge and who is acknowledged as its creators. This shift aims to cultivate an academic culture where knowledge is treated as a communal resource, and publications are used as tools to advance societal understanding and progress.